Leonurine (SCM-198) exerts protective effects on pancreatic β-cells in type 1 diabetes by modulating the Bax/Bcl-2/Caspase-3 signaling pathway - Zhiqi Li; XiaoRan Liu; FuJiang Wen; WenGuo Jiang; ZhenHong Xia (BMC Complementary Medicine and Therapies)
Abstract Background Type 1 diabetes mellitus (T1DM) is a disease marked by insulin deficiency and hyperglycemia, resulting from the destruction of pancreatic β-cells. The progression of T1DM is significantly influenced by oxidative stress and apoptosis. Natural compounds are highly effective in the treatment of T1DM and have multiple targets. The natural compound leonurine (SCM-198) possesses anti-inflammatory, anti-oxidant, and anti-apoptotic properties. However, the potential effect of SCM-198 in the treatment of T1DM has not been studied. Methods Our research aims to explore the therapeutic efficacy of SCM-198 in the context of T1DM through the integration of network pharmacology, molecular docking analyses, and both in vitro and in vivo experimental validation. In this study, we used pharmacokinetics to explore the druggability of SCM-198. The mechanisms through which SCM-198 exerts its effects on T1DM were explored using a network pharmacology approach. Subsequently, molecular docking simulations were employed to investigate the binding affinities of the core genes involved in SCM-198 treatment for T1DM. We established a mouse model of streptozotocin (STZ)-induced T1DM in vivo, and evaluated the therapeutic effect of SCM-198 on T1DM by blood glucose measurement, pathology and biochemical analysis, and further formalized the core pathway of SCM-198 regulation using STZ-damaged Min6 cells in vitro. Results Our findings showed that SCM-198 obeys Lipinski’s rule of five and exhibit desirable absorption, distribution, metabolism excretion and toxicity (ADMET) profiles. The core targets were significantly enriched in the apoptosis pathway. Molecular docking analysis revealed that Cysteine-aspartic Acid Protease 3 (CASP3), Tumor necrosis factor (TNF), and Matrix metallopeptidase 9 (MMP9) exhibited strong binding affinity for SCM-198. In vivo experiments, SCM-198 could not only reduce the fasting blood glucose (FBG), area under the glucose curve, blood lipid, liver function, and oxidative stress level in T1DM model mice, but also effectively improve the histopathological changes of pancreas and aorta. We further demonstrated that SCM-198 could protect Min6 cells from apoptosis by modulating the Bcl-2-associated X Protein (Bax)/B-cell Lymphoma 2 (Bcl-2)/Caspase-3 signaling cascade. Conclusion The present study demonstrated that SCM-198 exerts a protective effect on pancreatic β-cells in T1DM by attenuating apoptosis through inhibiting the Bax/Bcl-2/Caspase-3 signaling pathway. Therefore, SCM-198 holds great promise as a potential therapeutic candidate for T1DM.